Influenza and Pneumococcal Vaccination in Long Term Care Facilities in Two Regions of Quebec - Philippe De Wals; Michel Carbonneau; Hélène Payette; Théophile Niyonsenga (Canadian Journal of Infectious Diseases)
OBJECTIVES: To evaluate the use of influenza and pneumococcal vaccines in long term care facilities.